Postural exercise impaction on the development of vertebral curves and functional deformity for adolescent idiopathic scoliosis - Romadhoni, Dea Linia; Ramadhani, Alinda Nur (Universitas Muhammadiyah Purwokerto, 2025)
Background: Adolescent idiopathic scoliosis (AIS) is a common spinal deformity affecting children aged 10–18 years. Various treatment approaches, including specific exercises, bracing, surgery, traction, casting, and biofeedback, have been implemented to manage AIS. However, posture correction exercises remain a non-invasive rehabilitation strategy with the potential to prevent scoliosis progression and improve functional outcomes.Purpose: This study aimed to evaluate the effectiveness of posture correction exercises in reducing vertebral curvature deformity and improving functional abilities in adolescents with idiopathic scoliosis.Methods: This quasi-experimental study employed a one-group pretest-posttest design involving 30 students aged 10–15 years diagnosed with AIS. Participants underwent a four-week supervised posture correction exercise program. The primary outcome, vertebral curvature deformity, was assessed using the Adam’s Forward Bending Test, while changes in vertebral inclination angle were measured using a Scoliometer. All data were documented through structured questionnaires.Results: The findings revealed a statistically significant reduction in vertebral inclination angle following the intervention (p<0.001), indicating the effectiveness of posture correction exercises as part of scoliosis-specific rehabilitation programs.Conclusion: Posture correction exercises significantly reduce vertebral curvature deformity and enhance functional capabilities in adolescents with AIS. These findings support their integration into physiotherapy programs as a non-invasive rehabilitative and preventive approach for scoliosis management.